Light-Harvesting Metal-Organic Frameworks (MOFs) La-PTC for Photocatalytic Dyes Degradation - Agustino Zulys; Adawiah Adawiah; Jarnuzi Gunlazuardi; Muhammad Derry Luthfi Yudhi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
A novel porous metal organic framework, La-PTC was synthesized by solvothermal method using a perylene-3,4,9,10-tetracarboxylate ligand and lanthanum metal ion. The FTIR analysis showed that La-PTC has a different structure with PTCDA and Na4PTC. The La-PTC MOF has high crystallinity, bandgap energy of 2.21 eV with a maximum absorption area at 561 nm. A rod shape structure of La-PTC has been obtained with the surface area of 22.2364 m2.g−1 and classified into mesoporous material. The La-PTC was relative stable up to 376.93 °C. The La-PTC can degrade 64.76% of MO within ca. 240 min under visible light irradiation with the amount of 30 mg La-PTC. The addition of H2O2 improved the photocatalytic activity of La-PTC with degradation efficiency of 67.02%, 70.00%, and 99.60% for MB, RhB, and MO, respectively. This study presents the fabrication of the light-harvesting metal organic framework, La-PTC and its potential in dyes degradation. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).